COOPERATIVE LEARNING MODEL TYPE TEAM GAME TOURNAMENT (TGT) AND ITS INFLUENCE ON LEARNING OUTCOMES IN MATHEMATICS SUB-CHAPTER MULTIPLE : Case Study of Class II Lumansari State Primary School Kendal, Central Java - Widya Rahmawati Al-Nur; Eliza Katratun Nada (El Midad, 2023)
The purpose of this study was to determine whether the cooperative learning model of the Teams Game Tournament (TGT) type had an effect on the learning outcomes of Grade II Elementary School Student (EST) Number 2 Lumansari in the Mathematics subject of multiplication material. The research method used is an experiment with a quantitative approach. The form of design in this study is a Quasi-Experimental Design with a Nonequivalent Control Group Design research design. The population used in this study were Lumansari EST 2 students for the 2021/2022 school year, a total of 151 students. The sample studied was class II A of 15 students as the control class and class II B of 15 students as the experimental class. The sampling technique is random sampling. There are two data collection techniques used, namely observation sheets and tests. Based on the results of hypothesis testing with the help of SPSS using an independent sample t-test on the post-test data for the experimental class and the control class showed a sig. (2-tailed) of 0.000 <0.05, it can be concluded that Ho is rejected and H1 is accepted.